Microsprinkler Irrigation for Cold Protection of Florida Citrus - Lawrence R. Parsons; Brian J. Boman (EDIS)
Millions of boxes of fruit and thousands of acres of citrus trees have been lost in freezes and frosts. Oranges are usually damaged when the fruit are exposed to temperatures of 28°F or lower for 4 hours or more. As the temperature gets colder or durations below 28°F get longer, damage to fruit, leaves, twigs, and eventually large branches increases. More than nearly any other factor, freezes have caused some of the most dramatic changes in fruit supply, availability, and price. Thus, any method that provides some cold protection can be of major importance to citrus growers. This document is Fact Sheet HS-931, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: November 2003.